2013
DOI: 10.7205/milmed-d-12-00322
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dilute Dakin's Solution for the Treatment of Angioinvasive Fungal Infection in the Combat Wounded: A Case Series

Abstract: Disseminated fungal infections are normally opportunistic infections in the immunocompromised population. Current literature has documented a high mortality rate with these infections in civilian trauma or as complications of severe burns. There is only one published case of fungal infection in a combat-injured individual to date, which resulted in mortality despite aggressive debridement and appropriate antifungal agents. We present here three patients in whom aggressive debridement, antifungals, and the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
(24 reference statements)
1
26
0
Order By: Relevance
“…18 Treatment involves serial aggressive debridements, utilization of antifungal agents, and surgical amputation or revision of amputation levels when warranted. 1,5,6,15,17,20,21 Anecdotally, clinicians involved in the management of combat-related IFIs have noted that these infections generally lead to marked shortening of residual limbs, increased time and operative procedures prior to wound closure, and high rates of early complications. Nevertheless, as these factors have not yet been quantified, the impact of IFIs on those outcomes remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…18 Treatment involves serial aggressive debridements, utilization of antifungal agents, and surgical amputation or revision of amputation levels when warranted. 1,5,6,15,17,20,21 Anecdotally, clinicians involved in the management of combat-related IFIs have noted that these infections generally lead to marked shortening of residual limbs, increased time and operative procedures prior to wound closure, and high rates of early complications. Nevertheless, as these factors have not yet been quantified, the impact of IFIs on those outcomes remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a disinfectant in hospitals, animal facilities and in human drinking water supply, and serves as a bleaching agent and a food additive in industry. Sodium hypochlorite at 0.5% (Dakin's solution) was used with great success to control infections of combat wounded soldiers during World War I, before antibiotics , and was recently found effective in the treatment of wounded soldiers with potentially deadly angioinvasive fungal infections . The intermittent use of dilute sodium hypochlorite in “bleach baths” has shown efficacy as adjunctive therapy for atopic dermatitis .…”
mentioning
confidence: 99%
“…Interestingly, in one study wounds treated with DS also showed significantly increased neodermal thickness when compared with the controls, and greater numbers of proliferating fibroblasts [38]. Recently, in a small case series of military trauma patients, 0.025% DS was delivered with negative pressure wound therapy as an adjunct to aggressive debridement, and antifungals with clinical success [39]. The discrepancy between in vitro and in vivo studies is likely related to inactivation of sodium hypochlorite by the plasma components of the wound exudate, necessitating higher concentrations for in vivo efficacy, which was known by Carrel and Fleming [10,11].…”
Section: Discussionmentioning
confidence: 92%